2020
DOI: 10.3390/polym12030517
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Synuclein Amyloid Aggregation Is Inhibited by Sulfated Aromatic Polymers and Pyridinium Polycation

Abstract: The effect of a range of synthetic charged polymers on alpha-synuclein aggregation and amyloid formation was tested. Sulfated aromatic polymers, poly(styrene sulfonate) and poly(anethole sulfonate), have been found to suppress the fibril formation. In this case, small soluble complexes, which do not bind with thioflavin T, have been formed in contrast to the large stick-type fibrils of free alpha-synuclein. Sulfated polysaccharide (dextran sulfate), as well as sulfated vinylic polymer (poly(vinyl sulfate)) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The compounds were also non-toxic towards human neuroblastoma cell line making them very promising for treating synucleinopathies [57]. In a recent study, Medvedeva et al reported the ability of 3-methoxy-4-hydroxycinnamic acid (64), 3,4-dimethoxycinnamic acid (66) and 3-methoxy-4-acetamidoxycinnamic acid (82) (Figure 20) [57] to prevent alpha-synuclein amyloid transformation, thus aiding the treatment of Parkinson's disease [58]. The IC50 values of the compounds were 251 µM for 64, 50 µM for 82 and 13 µM for 2.…”
Section: Cinnamic Acid Derivatives With Neurological Activitymentioning
confidence: 99%
“…The compounds were also non-toxic towards human neuroblastoma cell line making them very promising for treating synucleinopathies [57]. In a recent study, Medvedeva et al reported the ability of 3-methoxy-4-hydroxycinnamic acid (64), 3,4-dimethoxycinnamic acid (66) and 3-methoxy-4-acetamidoxycinnamic acid (82) (Figure 20) [57] to prevent alpha-synuclein amyloid transformation, thus aiding the treatment of Parkinson's disease [58]. The IC50 values of the compounds were 251 µM for 64, 50 µM for 82 and 13 µM for 2.…”
Section: Cinnamic Acid Derivatives With Neurological Activitymentioning
confidence: 99%
“…Moreover, certain types of cationic dendrimers bind to monomeric forms of sheep prion [ 22 , 23 ] or beta-amyloid peptide [ 24 ], which prevents their further amyloid aggregation. Sulfated aromatic polymers inhibit the formation of alpha-synuclein fibrils in vitro [ 25 ], while sulfated polysaccharides inhibit the accumulation of amyloid aggregates of the prion protein in cell culture [ 26 ]. However, on the contrary, many polymeric molecules interacting with amyloidogenic proteins stimulate their pathological transformation.…”
Section: Effect Of Artificial Chaperones On the Pathological Transfor...mentioning
confidence: 99%
“…Kinetic of α-Syn bril formation was assessed in presence of 0 and 500 µM of each metal ion using ThT uorescence assay 41,42 . ThT uorescence assays were carried on a Cary Eclipse VARIAN uorescence spectrophotometer (Mulgrave, Australia).…”
Section: Thio Avin T Uorescence Assaymentioning
confidence: 99%